IMPLEMENTASI ADVOKASI, KOMUNIKASI DAN MOBILISASI SOSIAL (AKMS) DALAM PENCEGAHAN DAN PENANGGULANGAN TB PARU: Implementasi Advokasi, Komunikasi dan Mobilisasi Sosial (AKMS) Dalam Pencegahan dan Penanggulangan TB Paru - Nazifah Nazifah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2020)
Pulmonary TB disease is a disease that can cause death, the cause is a low level of Government support, a cadre of less socializing and community approaches and attitudes of pulmonary TB sufferer ashamed to do in treatment facilities the Ministry of health. Bengkalis Regency health centers already have the cadres but not yet running to its full potential it is seen with an increased incidence of pulmonary TB sufferer numbers every year despite not having a significant increase is due to yet the existence of public awareness in the Regency of Bengkalis. UPT Clinic and health services in the response and prevention of Tb has not been done properly.This research aims to find out how the implementation of advocacy, communication and social mobilization (AKMS) in the prevention and mitigation of pulmonary TB in bengkalis Regency in 2017. This study uses qualitative methods and aims to find out how an understanding of advocacy, communication and social mobilization (AKMS) in the prevention and mitigation of pulmonary TB dikabupaten bengkalis. This research was carried out in August-September 2017 in Bengkalis Regency health centers namely UPT UPT Clinic Bengkalis, UPT Health Center Selatbaru, UPT Health Center and Health Office Duku Dykes Regency of Bengkalis. Data analysis by means of triagulasi, methods and sources of data. Informants in this study amounted to 13 people. The results showed that the Government has yet to play a role in advocacy, communication and social mobilization have yet in the prevention of pulmonary TB has not been implemented well due to problems associated with the funds that are still lacking. Recommended for health services policy to conduct advocacy on the part of the Government and for the clinics to be able to do the Training and guidance, as well as cooperation with other health units